Utilization of Arbuscular Mycorrhizal Fungi (AMF) and Coconut Shell Charcoal to Increase Growth of Falcataria moluccana (Miq) Barneby & JW Grimes) and Samanea saman (Jacq) Merr Seedlings - Sri Wilarso Budi; Intan Fajar Kemala; Maman Turjaman (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Latosol soil has low fertility and widely spread out in Indonesia. The successful of planting activity on latosol soil can be supported by appropiate species selection and seedling good quality. The use of arbuscular mycorrhizal fungi (AMF) and coconut shell charcoal for improving sengon (Falcataria moluccana (Miq) Barneby & JW Grimes) and trembesi (Samanea saman ( Jacq) Merr growth is one alternative to support planting activities in latosol soil . This research was conducted in green house and used Split-Plot design of Complete Randomized Design (CRD) with AMF as a main plot and coconut shell charcoal as a sub-plot. Percentage of FMA colonisation, height, diameter, crown dry weight, root dry weight, ratio of crown root and quality index of seedlings were recorded. Results showed that interaction between AMF and coconut shell charcoal increased parameters growth for both seedling. Single factor from both AMF species (Glomus sp. and Gigaspora sp.) gives similar effect on growth of both seedling species.